Analisis Leverage, Firm Size, Deviden Payout terhadap Stock Price Volatility Pada Perusahaan LQ45 di BEI Tahun 2015-2019 - Arna Suryani (Universitas Batanghari Jambi, 2021)
This study examines and analyzes the effect of Leverage, Firm Size, Dividend Payout on Stock Price Volatility. This research was conducted on companies listed in the LQ45 index on the Indonesia Stock Exchange in 2015-2019. The sample was selected based on purposive sampling so that 27 sample companies were selected. Multiple linear regression analysis tool with classical assumption test and hypothesis testing. The results based on the analysis show that Leverage has a positive effect on Stock Price Volatility, while Company Size, Dividend Payout has a negative effect on Stock Price Volatility. This research can prove that the actions taken from the company's management can be seen from how the company should position the company's assets and liabilities as well as the distribution of dividends. This research is expected to make a positive contribution to all parties, especially investors in investing in the capital market while still paying attention to the level of leverage, company size and dividend payout ratio of the company to be invested.